Hemorragia postparto y su relación con atonía uterina en mujeres multíparas menores de 30 años del Hospital Dr. Nicolás coto infante de Vinces, Provincia de Los Ríos, periodo mayo-septiembre 2019 - Pazmiño Avilés, Laskmy Rayanny (2019)
In this final thesis report, the relationship between uterine atony and postpartum hemorrhage in multiparous women under 30 years of age, treated at Dr. Nicolás Coto Infante de Vinces Hospital, was determined in the period May-September 2019, in the development of this research, variables that give the feasibility of the study are treated. The information collection had as an analysis unit the medical records of the women treated in the hospital, so during the investigation, a sample of 169 women was worked, of which 79 pregnant women were treated by vaginal delivery and 90 attended By caesarean section, the data were collected intentionally and no formula was used to obtain the sample, so it was observed that they suffered from uterine atony and postpartum hemorrhage, whereby the stated objectives could be fulfilled and the respective conclusions obtained. . The type of research used was descriptive, retrospective, cross-sectional, so a system of actions will be developed aimed at medical personnel so that they can contribute to the decrease in the appearance of uterine atony and postpartum hemorrhages in multiparous women.